IMPACT OF FINANCIAL DISTRESS AND FINANCING CONSTRAINTS ON TRADE CREDIT - Tri Mulyana; Sung Suk Kim (FEB Universitas Sam Ratulangi Manado, 2023)
Purpose this study to examine the effect of (1) Financial Distress and (2) Financial Constraints on trade credit in companies listed on the Indonesia Stock Exchange (IDX). The Sampel in this study are all companies listed on the Indonesia Stock Exchange, except the banking and financing industries from 2020 to 2011. This study used the regression Fixed Effect Model to analyze secondary data from S&P Capital IQ. The study results show that (1) Financial Distress and Financial Constraint have a negative effect on Accounts Payable, (2) Financial Distress and Financial Constraint have a positive effect on Accounts Receivable.